Water sorption characteristics of a new type of gelatine powder, produced by a new high-pressure micronisation process - Reibe, Christian (Acta chimica slovenica, 2010)
A new high-pressure micronisation process for Gelatine has been developed. By applying this process to gelatine, a new type of Gelatine was produced: Dry and pure Gelatine powder of high molecular mass. This powder was investigated,regarding its sorption behaviour and compared to its feedstock material. The feedstock Gelatine was of type B 200 Bloom, 6 mesh, having a molecular mass of 150,000 g mol-1. The produced Gelatine powderćs molecular mass was around 130,000 g mol-1, while its mean particle size was 300 im. Their sorption isotherms were investigated at 30 °C, 40 °C and 60 °C and wateractivities in the range from 0.055 to 0.836. At given water activities the Equilibrium Moisture Contents (EMC) decreases with increasing temperature.The measured sorption isotherms were fit with the Brunauer- Emmet-Teller (BET)- model and the Guggenheim- Anderson- deBoer (GAB)- model. Both models described the adsorption behaviour well in their range of validity, while only the GAB-model was adequate for describing the desorption behaviour. Hysteresis effect occurred in each adsorption-desorption pair. The isosteric heat of sorption of both substances was determined for adsorption, desorption respectively. Slight differences in the sorption behaviour occurred due to processing, while quality of the gelatine was not affected.
Keywords: mikronizacija; sorpcijske lastnosti; želatina